2016
DOI: 10.4103/0366-6999.179792
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Alteration of Basal Ganglia in Different Forms of Primary Focal Dystonia

Abstract: Background:Few studies have addressed whether abnormalities in the lenticular nucleus (LN) are characteristic transcranial sonography (TCS) echo features in patients with primary dystonia. This study aimed to explore alterations in the basal ganglia in different forms of primary focal dystonia.Methods:cross-sectional observational study was performed between December 2013 and December 2014 in 80 patients with different forms of primary focal dystonia and 55 neurologically normal control subjects. TCS was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…In this study, we noticed that only 48 (7.36%, 48/652) PD patients were excluded due to insufficient transtemporal bone window, which is remarkably lower compared to other studies in the Asian population (7,29), but consistent with our previous studies (30)(31)(32). This may be because of the 2.5 MHz transducer we used (Sequoia 512, Siemens Medical Solutions USA, Inc. 4V1C transducer), which was compared with other transducers and showed the best penetration.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we noticed that only 48 (7.36%, 48/652) PD patients were excluded due to insufficient transtemporal bone window, which is remarkably lower compared to other studies in the Asian population (7,29), but consistent with our previous studies (30)(31)(32). This may be because of the 2.5 MHz transducer we used (Sequoia 512, Siemens Medical Solutions USA, Inc. 4V1C transducer), which was compared with other transducers and showed the best penetration.…”
Section: Discussionsupporting
confidence: 90%
“…One transcranial sonography study of the SN revealed the existence of hyperechography in DRD ( 40 ) and DYT6 ( 41 ) that was similar to that observed in PD cases. However, another study reported no sonographic alterations in cervical dystonia and blepharospasm ( 42 ). Taken together, the studies on generalized and segmental dystonia, including our study, showed abnormality of the SN and no change in focal dystonia, including cervical dystonia and blepharospasm.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with PD, hyperechogenicity of the LN has been reported more frequently in atypical parkinsonism, including the parkinsonian phenotype of a multiple system atrophy or progressive supranuclear palsy [ 44 , 45 ]. Interestingly, LN hyperechogenicity has also been described in patients with Wilson’s disease [ 46 ], Creutzfeldt–Jakob disease [ 47 ], primary focal dystonia [ 48 ], Fahr’s disease [ 49 ], and pantothenate kinase-associated neurodegeneration [ 50 ]. This would suggest a common, or at least a similar, pathomechanism underlying LN hyperechogenicity, which might lie in an iron–copper–calcium accumulation and the subsequent gliosis [ 43 , 46 ].…”
Section: Discussionmentioning
confidence: 99%